Visible-Light-Driven Photocatalytic Degradation of Aniline over NaBiO3 - Guo Liu; Zhen Wang; Wenjie Zheng; Shaogui Yang; Cheng Sun (Advances in Condensed Matter Physics)
Aniline was almost completely degraded in 30 min in given conditions. It was found that pH and NaBiO3 dosage had played important role in the photocatalytic degradation. To scrutinize the mechanistic details of the aniline photodegradation, several critical analytical methods including spectroscopy and GC/MS were utilized to detect the temporal course of the reaction. Intermediates and several small molecular products were separated and identified, such as C2H5O3N, C10H13O2N, and C12H10N2. Then two possible photodegradation pathways of aniline over NaBiO3 were proposed: ring opening and mineralization.